2023
DOI: 10.3390/agriculture13061274
|View full text |Cite
|
Sign up to set email alerts
|

The Vertical Price Transmission in Pork Meat Production in the Czech Republic

Abstract: The paper aims at vertical price transmission of the agri-food market in the Czech Republic. It is focused on the analysis of price transmission in pork meat by investigating the short-run and long-run relationships within the product and the speed of establishing the equilibrium relationship. For this purpose, there is employed specially VECM (Vector Error Correction Model), impulse-response analysis, and decomposition of variance of VECM, which show the system’s reaction. The applied approach considers five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…In order to assess the causal relationships between the study variables, we imposed a set of restrictions on the augmented VAR model, shown in Equation (11). Table 1 presents the specifications for both the null and alternative hypotheses, outlining the constraints imposed on the matrix coefficients as defined in Equation (11).…”
Section: Causality Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to assess the causal relationships between the study variables, we imposed a set of restrictions on the augmented VAR model, shown in Equation (11). Table 1 presents the specifications for both the null and alternative hypotheses, outlining the constraints imposed on the matrix coefficients as defined in Equation (11).…”
Section: Causality Testsmentioning
confidence: 99%
“…Surging price spillovers have the potential to lead to high inflation rates, large trade deficits, and unfavorable macroeconomic environments, especially in developing economies [6]. A thorough understanding of commodity price spillovers is essential for navigating global markets [7], predicting trends [8], managing financial risks [9,10], and fostering sustainable agricultural practices [11] to enhance economic resilience and food security overall. The importance of investigating price and volatility transmission dynamics across diverse commodity markets is evident based on the attention it has consistently received in the literature over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigaciones sobre la transmisión espacial y vertical de precios, de diferentes productos, siguen teniendo lugar en todo el mundo (Deb et al 2020, Hillen 2021, Sirohi et al 2023 Ecosist. Recur.…”
Section: Introductionunclassified
“…Fluctuations in feed prices, which are an upstream component of the pork industry chain, are the main factors driving pork price fluctuations. Additionally, the pork price exhibits seasonal characteristics [7][8][9][10]. Zhang et al [11] and Hayes et al [12] further suggested that seasonal price changes in pork may result from variations in pork supply, changes in consumer demand for pork products, and a combination of supply and demand factors.…”
Section: Introductionmentioning
confidence: 99%